Intrinsic Motivation and Nursing Performance: A Quantitative Study of the Mediating Effect of Organizational Citizenship Behavior - Mursaha, Istikama; Alhadar, Fadhliah M.; Soleman, Marwan Man (Journal of International Conference Proceedings, 2025)
This study aims to examine the influence of intrinsic motivation on the performance of nursing staff, with Organizational Citizenship Behavior (OCB) serving as a mediating variable at Weda Regional General Hospital, Central Halmahera Regency. The study employs a quantitative approach, with a population of 324 employees and a sample consisting of 106 nursing staff. The sample was selected using purposive sampling, and the data were analyzed using path analysis (path modeling) with the aid of SmartPLS version 4. The findings indicate that: (1) intrinsic motivation has a positive and significant effect on nursing staff performance; (2) intrinsic motivation positively and significantly affects OCB; (3) OCB has a positive and significant effect on nursing staff performance; and (4) OCB functions as a partial mediator in the relationship between intrinsic motivation and nursing staff performance.